Pengaruh Audit Badan Pemeriksa Keuangan Terhadap Pengelolaan Keuangan Daerah (Studi pada Badan Pengelolaan Keuangan dan Asset Kabupaten Pamekasan) - Mukhlisotunnisak, Mukhlisotunnisak (Jurnal Administrasi Publik, 2016)
Abstract: The influence of Financial Auditor Board’s Audit on District Financial Management (Study on Board of Financial and Asset Management at Pamekasan Regency). This research purpose is to find out the influence of Board of Financial Auditor’s (BPK stands for Badan Pemeriksa Keuangan) opinion toward the district government financial report. Quantitative method was mainly applied in this research, with using total sampling technique. Data collection technique used in this research focused mainly on questionnaire and documentation. Simple regression analysis was used to analyze the data collected and finally t-test was used to test the research hypotheses. Simple regression analysis revealed that there exist a significant correlation between the variables. It showed by the value of coefficient correlation (R) at the degree equals to 0.628. The model ability on explaining the influence of independent variable toward dependent variable showed by the value of R square (R2) at the degree equals to 0.394. t-test analysis showed that there is a positive influence of independent variable (BPK’s opinion) on dependent variable (district government’s financial report). In other phrase, the better the opinion of BPK’s opinion, the better the district government’s financial report.   Keywords: Board of Financial Auditor’s (BPK) audit, district financial management, BPK’s opinion, district government’s financial report. Abstrak: Pengaruh Audit Badan Pemeriksa Keuangan Terhadap Pengelolaan Keuangan Daerah (Studi pada Badan Pengelolaan Keuangan dan Asset Kabupaten Pamekasan). Tujuan dari penelitian ini untuk mengetahui pengaruh opini Badan Pemeriksa Keuangan (BPK) terhadap laporan keuangan pemerintah daerah. Penelitian ini dilakukan dengan menggunakan metode kuantitatif, pengambilan sampelnya dengan teknik total sampling. Dimana teknik pengumpulan data yang digunakan adalah kuesioner dan dokumentasi. Serta Teknik analisis data yang digunakan adalah analisis regresi sederhana dan uji hipotesisnya menggunakan uji t. Hasil analisis regresi sederhana menunjukkan tingkat hubungan yang berarti antar variabel dilihat dari nilai koefisien korelasi (R) sebesar 0,628. Kemampuan model dalam menjelaskan pengaruh variabel bebas terhadap variabel terikat dapat dilihat pada nilai R Square (R2) yaitu sebesar 0,394. Hasil uji t menunjukkan adanya pengaruh yang positif dari variabel bebas (opini BPK) terhadap variabel terikat (laporan keuangan pemerintah daerah). Artinya, semakin baik opini BPK akan mengakibatkan semakin baik pula laporan keuangan pemerintah daerah.   Kata kunci: audit Badan Pemeriksa Keuangan (BPK), pengelolaan keuangan daerah, opini BPK, laporan keuangan pemerintah daerah